1997
DOI: 10.1111/j.1442-2042.1997.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Subtypes and Receptor‐Coupled Phosphatidylinositol Hydrolysis in Rat Bladder Smooth Muscle

Abstract: M2 and M3 receptors are expressed in rat urinary bladder. Only M3 receptor was involved in the production of IP3, which might induce the initial phase of contractile response in rat bladder smooth muscle after carbachol stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…Many studies have reported nonspecific increases in responsiveness of the detrusor muscle strip in STZ-induced DM in rats. 12,13 Luheshi and Zar 11 reported enhanced release of acetylcholine in detrusors of STZ-induced diabetic rats. Increased acetylcholine release can upregulate the muscarinic receptors in the diabetic detrusor muscle.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have reported nonspecific increases in responsiveness of the detrusor muscle strip in STZ-induced DM in rats. 12,13 Luheshi and Zar 11 reported enhanced release of acetylcholine in detrusors of STZ-induced diabetic rats. Increased acetylcholine release can upregulate the muscarinic receptors in the diabetic detrusor muscle.…”
Section: Discussionmentioning
confidence: 98%
“…12 Several studies have reported increased responsiveness of DM bladder strips to externally applied muscarinic agonists. 21,22 Tong et al 23 showed a significant increase in muscarinic receptor density in detrusor muscle in diabetic rats at both 2 and 8 weeks following the induction of DM. Conversely, Malmgren et al 24 showed a decrease or no change in the muscarinic component of the motor control of the bladder.…”
Section: Detrusor Smooth Muscle Dysfunction In Dmmentioning
confidence: 96%
“…As men-PHARMACOLOGY OF THE LOWER URINARY TRACT tioned previously, neuronal stimulation releases both acetylcholine and ATP in most animal bladders, whereas in the normal human detrusor, neurally mediated contractions are thought to occur predominantly through the actions of acetylcholine (Andersson, 1993). In rabbit and rat rabbit detrusor, ATP and acetylcholine have been proposed to cause either or both extracellular Ca 2ϩ influx and release from stores (Andersson, 1993;Munro and Wendt, 1994;Yu et al, 1996;Mimata et al, 1997). In human detrusor smooth muscle, the contribution of intracellular store release and extracellular influx to cholinergic responses often differs between studies (Andersson, 1993;Harriss et al, 1995;King et al, 1998;Masters et al, 1999;Wu et al, 1999;Visser and van Mastrigt, 2000).…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…In bladders from diabetic animals, an increased density of muscarinic receptors accompanied by an enhanced muscarinic receptor-mediated phosphoinositide hydrolysis was found (Latifpour et al, 1989;Mimata et al, 1995). An up-regulation of M 2 receptor mRNA has been demonstrated in rats with streptozotocin-induced diabetes (Tong et al, 1999), and also a supersensitivity of postjunctional muscarinic receptors may develop .…”
Section: Peripheral Targetsmentioning
confidence: 99%